Recent developments in the energy poverty and vulnerability research in Europe: a systematic literature review - Tuija Kajoskoski; Kaisa Matschoss; Eva Heiskanen; Senja Laakso (Energy Strategy Reviews)
There is an extensive body of energy poverty literature in the European context, and the literature is increasing at a fast pace. This is due to increased awareness of the problem, as well as societal developments such as the energy transition and recent geopolitical instabilities. However, the development of energy poverty research targeting households in the European context has not been systematically examined. This review fills the gap in current literature by providing a comprehensive analysis of the academic energy poverty research in Europe. We focus on two time periods: 2010–2020 and 2021–2023 and compare the two data sets for similarities and differences in contextual motivations, definitions of energy poverty and energy vulnerability, theoretical literatures, causes of energy poverty, groups identified as poor or vulnerable, and proposed solutions. The findings show that the literature is characterised more by continuity than evolution, yet we identified several important developments. We found that research increasingly understands energy poverty and vulnerability as structural issues and as reflective of divisive societal inequalities. Recent research is increasingly drawing on broader social science literature on inequality to study intersections of various forms of energy vulnerability. Moreover, these vulnerabilities and inequalities ensuing from the energy transition have emerged as persistent problems on research and policy agendas. Future research should continue to examine the links between energy transitions, energy vulnerability and energy justice to identify new vulnerabilities and the wider social impacts of the changing energy system.